Analisa Kinerja Localizer Sebagai Instrument Landing System Dari Perspective Rangkaian Elektronika Telekomunikasi - Karimansyah Putra; Indra Yasri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Instrument Landing System is navigational aids aircraft landing, localizer is part of the ILS function to provide information of air straightness on the runway. This paper discusses the localizer performance in the perspective of telecommunication electronics i.e. the series of power amplifier and recombiner monitoring. The proposed method through a modelling of the manufacturer's specifications and compared to the field measurement. Overall, the comparison result shows within the manufacturing specification with indicating less than 0,2% error.Keywords : Instrument Landing System, Localizer, Power Amplifier, Monitor Recombiner.